HRM in the German business system: A review - Angelo Giardini; Rüdiger Kabst; Michael Müller-Carmen (Management Revue, 2005)
Human resource management in Germany is deeply rooted in its institutional environment. Thus, US style HRM cannot be simply transferred to the German context. Nevertheless, the German business system is not hostile to HRM principles. Rather, these practices have to be adapted to the demands and constrains of the German socio-economic context. The key labour market institutions of collective bargaining, co-determination, and initial vocational training in particular require a pluralist style of human resource management. As our review suggests, these institutions support the implementation of some HRM principles while inhibiting others. Also, the concept of Strategic HRM in Germany may only be fully understood against the background of labour market institutions.
Keywords: 650; HRM; national business system; neo-institutionalism; industrial relations; Germany; Personalmanagement; Arbeitsbeziehungen; Wirtschaftsordnung; Neue Institutionenökonomik; Deutschland